Doing a successful research project : using qualitative or quantitative methods - Davies, Martin Brett, 1936- 4 0 16; 5 (Houndmills : Palgrave Macmillan, 2007)
Presents a guide to research methods, from planning to design, implementation, and completion of a project that involves quantitative or qualitative research and analysis.
Includes bibliographical references (p. 267-269) and index.
Keywords: 2 -- 0; 6; Research. -- Social sciences;Qualitative research. -- 20; 20; 2